To flee or not to flee: characterising differentiated anti-predatory responses of two mangrove crabs. Issue 2 (4th March 2017) - Su, Theresa L.; Lim, Shirley S.L.
Abstract : In a previous study, lethal effects of mudskipper (predator) presence were detected in the mangrove brachyuran Paracleistostoma depressum but not Haberma nanum . In addition, these effects were sex specific (male: non-significant; female: significant), suggesting differences in anti-predator behaviour. To validate this, predator avoidance strategies of the two prey species were investigated for the variables 'species' and 'sex'. Ex situ responses of 40 crabs (10 per sex per species) to a mudskipper model were video-recorded. Three stimuli were given in the sequence of (A) upper torso appearance, (B) full body appearance and (C) lunge towards crab. Innate behaviour to any innocuous signal was ruled out by replacing the mudskipper model with a rectangular block. Lastly, predator recognition capabilities in terms of shape and presence of eyes were tested using five models with increasing similarity to the predator model. P. depressum and H. nanum share the same suite of observable anti-predatory behaviours: "freeze", "sit" or "run". However, varied strategies were observed. Instead of flight, P. depressum "sit", and reacted most notably in the last stimulus. In contrast, H. nanum reacted early in the onset of impending threat with "run", with diminished responses despite the increase in signal strength. Contrary to prediction, the factor 'sex' was not statistically significant in either species. Predator recognition capabilities were ascertained in both prey species, as behaviours were different after the predator model was replaced. H. nanum displayed greater sensitivity for threat perception by withholding the flight behaviour when uncertain. This keen sense for threat recognition coupled with its flight strategy may be key to explaining the exclusion of H. nanum from the predator's diet.